RESPON SISWA KELAS IX BERDASARKAN TAKSONOMI SOLO DALAM MENYELESAIKANSOAL BANGUN RUANG SISI LENGKUNG YANG DISUSUN SESUAI DENGAN TAKSONOMI BLOOM DI SMP NEGERI 1 MARGOMULYO BOJONEGORO - Sriyati, Sriyati; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: The frameworks of classifying statements to predict the studentsâ learning ability are Bloomâs Taxonomy and SOLO Taxonomy. Bloomâs Taxonomy is made for educational purpose, while SOLO Taxonomy is used for the reference in analyzing the response of learners.The purposes of this research were to know about the IX gradestudentsâ responses in solving geometry curved size based on Bloomâs Taxonomy and SOLO Taxonomy. The research method was qualitative and the data resourcesware eleven students of SMP Negeri 1 Margomulyo, Bojonegoro. The results of this research showed that the studentsâ response in understanding aspect on pre-structural level are 18,2%, uni-structural level are 9,1%, multi-structural level were 9,1%, relational level are 54,5%, and extended abstract level are 9,1%.Â  None of he students response in applying aspect on pre-structural level,uni-structural level are 9,1%, multi-structural level are 54,5%, relational level are 18,2%, extended abstract level are 18,2%.The studentsâ response in analyzing aspect on pre-structural level are 27,3%, uni-structural level are 9,1% multi-structural level are 9,1%, relational level are 36,4%, and extended abstract levelare18,2%. The students on the same level were not necessarily showed the same response.Keywords: Studentsâ response, Geometry curved sized, Bloomâs Taxonomy, SOLO Taxonomy.Â